2016
DOI: 10.1097/mcg.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity-specific Disparities in Hepatocellular Carcinoma Stage at Diagnosis and its Impact on Receipt of Curative Therapies

Abstract: Among US adults with HCC, blacks consistently had more advanced stage at diagnosis and lower rates of receiving treatment. After correcting for cancer stage and evaluating the subset of patients eligible for curative therapies, blacks and Hispanics had significantly lower rates of curative HCC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 34 publications
5
69
1
Order By: Relevance
“…As demonstrated in previous studies, compared to non-Hispanic Whites we found a poor survival in African Americans and a good survival in Asian patients [4, 7, 9, 12, 15, 16]. Our results demonstrate that increased presence of large tumor size was associated with poor survival in African Americans.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As demonstrated in previous studies, compared to non-Hispanic Whites we found a poor survival in African Americans and a good survival in Asian patients [4, 7, 9, 12, 15, 16]. Our results demonstrate that increased presence of large tumor size was associated with poor survival in African Americans.…”
Section: Discussionsupporting
confidence: 88%
“…Tumor size is considered as an important prognostic determinant in several HCC staging systems such as the TNM classification [17], the Barcelona Clinic Liver Cancer (BCLC) staging system [18], and the Hong Kong Liver Cancer (HKLC) classification [19]. Although previous studies have reported the significant differences in tumor size in HCC patients stratified by race and proposed it as a predictor of prognosis for HCC patients [4, 7, 9, 12, 15, 16], our study has demonstrated that tumor presentation indeed is the dominant contributor to the poor OS of African Americans. Such a clear dominant factor could not be demonstrated for Hispanic-Whites and Asians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Racial/ethnic disparities have been reported both in NAFLD and HCC: Hispanics tend to have a more progressive course in NAFLD; and have lower rates of curative therapies for HCC[13]. Our finding that Hispanic ethnicity was associated with a decreased risk of development of HCC within NAFLD is surprising and needs confirmation with a larger cohort of individuals with NASH and other etiologies of chronic liver disease.…”
Section: Discussionmentioning
confidence: 51%
“…However, racially diverse, socioeconomically disadvantaged patients represent a difficult-to-reach population and are an important population to study given they experience health disparities, including higher HCC incidence and mortality rates 19, 33, 34 and lower HCC surveillance rates. 35-37 Outreach interventions would likely be equally, if not more, successful in other patient populations. Second, patients may have received HCC screening tests at outside institutions, although this is unlikely because many patients did not have insurance and would have out-of-pocket costs for outside testing.…”
Section: Discussionmentioning
confidence: 99%